2018
DOI: 10.1097/ccm.0000000000003279
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Effect of Probiotics on Cytokine Levels in Critically Ill Children With Severe Sepsis: A Double-Blind, Placebo-Controlled Trial*

Abstract: Probiotics supplementation for 7 days resulted in significant decrease in proinflammatory and increase in antiinflammatory cytokines in children with severe sepsis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
43
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 54 publications
(46 citation statements)
references
References 51 publications
3
43
0
Order By: Relevance
“…Our results demonstrated that early immune monitoring at PICU admission could help to identify those patients with better prognosis. In this setting, we demonstrated that IL-6 levels (with higher 39.32 pg/ml) have a high negative predictive value of prognosis in nonseptic critically ill children, which was consistent with the results of previous studies in neonatal/pediatric critically ill patients with sepsis [ 16 , 17 ]. CRP was a routinely measured inflammatory marker.…”
Section: Discussionsupporting
confidence: 92%
“…Our results demonstrated that early immune monitoring at PICU admission could help to identify those patients with better prognosis. In this setting, we demonstrated that IL-6 levels (with higher 39.32 pg/ml) have a high negative predictive value of prognosis in nonseptic critically ill children, which was consistent with the results of previous studies in neonatal/pediatric critically ill patients with sepsis [ 16 , 17 ]. CRP was a routinely measured inflammatory marker.…”
Section: Discussionsupporting
confidence: 92%
“…Accumulating studies have demonstrated that inulin may increase proportions of Bifidobacterium and Lactobacillus [32,34]. Probiotic Bifidobacterium possessed capable of suppression of pro-inflammatory cytokine synthesis [35][36][37]. We also found that inulin elevated this beneficial Bifidobacterium, revealing that inulin may ameliorate PCOS by improving the proportion of Bifidobacterium.…”
Section: Discussionmentioning
confidence: 59%
“…At the same time, emerging data have shown that probiotics can secrete metabolites and factors with immunomodulatory properties [24,48,64]. For example, relevant studies demonstrated a decrease in proinflammatory cytokines using multistrain probiotic supplementation [21,65,66]. The novelty in our study was that we used an inexpensive food (and easily produced at home) to reduce serum proinflammatory cytokines and possibly contribute to neuroprotective effect in AD patients.…”
mentioning
confidence: 99%